Combatting infectious diarrhea: innovations in treatment and vaccination strategies - Vivek P. Chavda; Suneetha Vuppu; Toshika Mishra; Sathvika Kamaraj; Nikita Sharma; Swati Punetha; Anand Sairam; Dixa Vaghela; Narges Dargahi; Vasso Apostolopoulos (Taylor & Francis Group, 2024)
ABSTRACTIntroduction The escalating prevalence of infectious diseases is an important cause of concern in society. Particularly in several developing countries, infectious diarrhea poses a major problem, with a high fatality rate, especially among young children. The condition is divided into four classes, namely, acute diarrhea, invasive diarrhea, acute bloody diarrhea, and chronic diarrhea. Various pathogenic agents, such as bacteria, viruses, protozoans, and helminths, contribute to the onset of this condition.Areas covered The review discusses the scenario of infectious diarrhea, the prevalent types, as well as approaches to management including preventive, therapeutic, and vaccination strategies. The vaccination techniques are extensively discussed including the available vaccines, their advantages as well as limitations.Expert opinion There are several approaches available to develop new-improved vaccines. In addition, route of immunization is important and aerosols/nasal sprays, oral route, skin patches, powders, and liquid jets to minimize needles can be used. Plant-based vaccines, such as rice, might save packing and refrigeration costs by being long-lasting, non-refrigerable, and immunogenic. Future research should utilize predetermined PCR testing intervals and symptom monitoring to identify persistent pathogens after therapy and symptom remission.